Epidemic characteristics of food poisonings in Yunnan province, 2004 - 2019 - Xiu-lian SHEN; Shan-hua YANG; Xia PENG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore epidemic characteristics of food poisonings reported in Yunnan province and to provide evidences for developing strategies on the prevention and control of food poisoning.MethodsFrom the Public Health Emergency Reporting System, a subsystem of the China Information System for Disease Control and Prevention, we extracted all data on food poisoning-related public health emergencies in Yunnan province reported from 2004 through 2019 for a descriptive epidemiological analysis.ResultsTotally 1 014 food poisoning incidents were reported in the province during the 16-year period; the incidents involved 27 965 sufferers and 864 mortalities, with a fatality rate of 3.09%. Of all the incidents, 45.17% (458) occurred during June - August in a year, a season with more food poisoning caused by intake of toxic wild mushrooms. More than a half (56.48%, 488 deaths) of the food poisoning mortalities were due to poisonings associated with toxic wild mushrooms. Three minority autonomous prefectures (Wenshan, Honghe and Chuxiong prefectures) were among the top five regions with more food poisonings and the number of reported food poisonings was 143, 100, and 97 for the three prefectures, respectively. Homes and schools in rural regions were top two settings with higher food poisoning incidents and 520 (51.28%) and 181(17.85%) of all the reported incidents occurred at the two settings. For all the reported food poisonings, more than one third (39.94%, 11 168) of the all sufferers were associated with dinner parties and the most (85.42%, 733) of the mortalities were related to home settings in rural regions.ConclusionDuring 2004 - 2019 in Yunnan province, the incidence rate of food poisonings was relatively high in prefectures (municipalities) heavily or scatteredly inhabited by ethnic minorities; the epidemic peaks for the food poisoning were observed during June - August in a year; the most of the mortalities due to the food poisonings was associated eating toxic wild mushrooms and more food poisoning occurred in home and school settings in rural regions. The results suggest that in food poisoning prevention, special concerns should be paid to health education on food hygiene and wild mushroom poisoning in minority regions and rural home and school settings.